Plasticity of human handedness: Decreased one-hand bias and inter-manual performance asymmetry in expert basketball players - Stöckel, T.; Weigelt, M. (Journal of Sports Sciences, 2012)
Athletes frequently have to adapt their skills to fast changes of play, often requiring the flexible execution of a particular movement skill with either hand. To assess the influence of sport-specific expertise and extensive sport training on human laterality, a video analysis of regular basketball games was performed for professional, semi-professional, and amateur players to investigate how non-dominant hand use and proficiency change with increasing expertise. Our results showed that the right-hand (i.e. dominant hand) bias in basketball players is reduced with increasing expertise (i.e. competitive level). Accordingly, we found that professional players use their non-dominant hand more often and with greater success than semi-professional and amateur players. This was true for most of the basketball-specific skills. Based on these results, we assume that increasing amounts of bilateral practice can lead to a shift in task-specific manual preference towards a higher use of both hands in competition, as well as to a higher proficiency for non-dominant hand actions in particular. From an applied perspective, the more frequent use and higher proficiency of the non-dominant hand in professional basketball players, compared with amateurs, suggests that the context-specific and skilled use of the non-dominant hand is crucial for successful play at higher competitive levels in the sport of basketball.